Architectural Design with A Phenomenological Approach, A Case of Museum Sensory Experience - Maryam Al-Madhi; Najl Allani (Proceedings of the International Conference of Contemporary Affairs in Architecture and Urbanism-ICCAUA)
The phenomenological approach's role is to implement human perceptions where humans exist by perceiving and observing the surrounding in a body relation with the built environment and world surroundings, as Ponty’s philosophy addresses. Furthermore, architecture is the overall image of emerging human life aspects connected with all human sensations that reflect perceptions, experiences, and ideas. Significantly, attributes of daily experiences exist through architecture and social aspects. The purpose of the study stands to understand bodily experience through phenomenological approaches in a museum. For instance, surrounded built environment and designed atmosphere in architectural design and human sensation concerning phenomenological characteristics. In addition, phenomenological methodology through focus groups is properly considered while practising the museum's journey that attracts the user’s sensory experience and perceptions. Moreover, the study analysis results concerning human sensations and design aspects in a museum experience are promised with design awareness.